Juden und Nichtjuden nach der Shoah Begegnungen in Deutschland - Fischer, Stefanie; Riemer, Nathanael; Schüler-Springorum, Stefanie (Europäisch-jüdische Studien - Beiträge, 2019)
Given what we know about Nazi crimes of violence, it is hard for us to imagine encounters between Jews and non-Jews after 1945. Yet many connections developed between Holocaust survivors, refugees, hangers-on, observers, and profiteers. The volume examines relationships in civil society between Jewish and non-Jewish Germans from a historical and cultural historical perspective.